Ekonomi Malaysia : satu analisis dasar - Jamal Ali. (Kuala Lumpur : Dewan Bahasa dan Pustaka, 2003)
Economy of Malaysia.
Includes bibliographical references (p. 305-308) and index.
In Malay.
Keywords: Malaysia -- Economic policy; Malaysia -- Economic conditions